Digitalization of intangible cultural heritage in the era of disruption: Utilization of social media in cultural preservation and education in schools - Febrianto, Priyono Tri; Puspitasari, Aditya Dyah; Pritasari, Ade Cyntia; Razali, Asbah; Sulaiman, Sabri (Jurnal Sosiologi Dialektika, 2025)
The rapid advancement of digital technology has challenged conventional models of cultural preservation, particularly in safeguarding intangible cultural heritage (ICH). This study aims to analyze the digitization of ICH in the era of disruption through the utilization of social media as a strategy for cultural preservation and education in elementary schools in Sumenep District, Indonesia. Employing a mixed-methods approach, the research involved 187 elementary students through structured surveys and 17 key informants through in-depth interviews. Quantitative data were processed using SPSS, while qualitative data were thematically coded and interpreted. The findings demonstrate that while students possess a general understanding of ICH, conceptual depth remains uneven, particularly regarding ICH's philosophical, spatial, and identity dimensions. Social media platforms—primarily YouTube, TikTok, and Instagram, play a pivotal role in enhancing students’ engagement with cultural content, especially when the content is presented in visual-textual formats. Both teachers and students reported significant positive impacts, including improved cultural awareness, creativity, and appreciation for national identity. However, minor negative implications were also noted, such as distraction and misinformation. The study confirms that social media, when strategically integrated into pedagogy, enhances access to ICH knowledge and fosters cultural resilience among younger generations. In conclusion, the integration of digital platforms into cultural education constitutes an effective mechanism for preserving ICH and cultivating intergenerational cultural continuity in the digital age.